Efficient Generation of Microdroplets Using Tail Breakup Induced with Multi-Branch Channels - Daiki Tanaka; Satsuki Kajiya; Seito Shijo; Dong Hyun Yoon; Masahiro Furuya; Yoshito Nozaki; Hiroyuki Fujita; Tetsushi Sekiguchi; Shuichi Shoji (Molecules, 2021)
In recent years, research on the application of microdroplets in the fields of biotechnology and chemistry has made remarkable progress, but the technology for the stable generation of single-micrometer-scale microdroplets has not yet been established. In this paper, we developed an efficient and stable single-micrometer-scale droplet generation device based on the fragmentation of droplet tails, called “tail thread mode”, that appears under moderate flow conditions. This method can efficiently encapsulate microbeads that mimic cells and chemical products in passively generated single-micrometer-scale microdroplets. The device has a simple 2D structure; a T-junction is used for droplet generation; and in the downstream, multi-branch channels are designed for droplet deformation into the tail. Several 1–2 µm droplets were successfully produced by the tail’s fragmentation; this continuous splitting was induced by the branch channels. We examined a wide range of experimental conditions and found the optimal flow rate condition can be reduced to one-tenth compared to the conventional tip-streaming method. A mold was fabricated by simple soft lithography, and a polydimethylsiloxane (PDMS) device was fabricated using the mold. Based on the 15 patterns of experimental conditions and the results, the key factors for the generation of microdroplets in this device were examined. In the most efficient condition, 61.1% of the total droplets generated were smaller than 2 μm.